Effects of proteasome inhibitors MG132, ZL3VS and AdaAhx3L3VS on protein metabolism in septic rats. - Kadlcíková, J; Holecek, M; Safránek, R; Tilser, I; Kessler, B (2004)
Proteasome inhibitors are novel therapeutic agents for the treatment of cancer and other severe disorders. One of the possible side effects is influencing the metabolism of proteins. The aim of our study was to evaluate the influence of three proteasome inhibitors MG132, ZL(3)VS and AdaAhx(3)L(3)VS on protein metabolism and leucine oxidation in incubated skeletal muscle of control and septic rats. Total proteolysis was determined according to the rates of tyrosine release into the medium during incubation. The rates of protein synthesis and leucine oxidation were measured in a medium containing L-[1-(14)C]leucine. Protein synthesis was determined as the amount of L-[1-(14)C]leucine incorporated into proteins, and leucine oxidation was evaluated according to the release of (14)CO(2) during incubation. Sepsis was induced in rats by means of caecal ligation and puncture. MG132 reduced proteolysis by more than 50% and protein synthesis by 10-20% in the muscles of healthy rats. In septic rats, proteasome inhibitors, except ZL(3)VS, decreased proteolysis in both soleus and extensor digitorum longus (EDL) muscles, although none of the inhibitors had any effect on protein synthesis. Leucine oxidation was increased by AdaAhx(3)L(3)VS in the septic EDL muscle and decreased by MG132 in intact EDL muscle. We conclude that MG132 and AdaAhx(3)L(3)VS reversed protein catabolism in septic rat muscles.